New insights into membrane science and technology : polymeric and biofunctional membranes - Bhattacharyya, D. (Dibakar), 1941-; Butterfield, D. Allan (Membrane science and technology series, 2003)
Membrane techniques provide a broad science and technology base. Although there are several books in the traditional membrane field, there is a great need for a highly comprehensive book. This refereed book covers materials from highly respected researchers. This title is highly multidisciplinary in nature and should be extremely valuable to scientists and engineers involved in a variety of activities. Students and faculty members around the world will find this title to be an excellent reference book. - Invited contributions from leading researchers in the field. - Coverage of topic is of value to scientists/engineers working in a variety of related fields [separations/reactions, advanced biofunctional materials, contactor designs]. - Aims to fill market gap for a highly comprehensive book containing advances in both synthetic and biofunctional/bimimetic membranes.